Korean soap operas in Latin America a cultural studies approach (2015)
The consumption of Korean soap operas in Latin America is part of the phenomenon of cultural globalization that characterizes the current social world. From the field of Cultural Studies we address the issue with the objective of reflecting on the intercultural communication that is conveyed from the penetration of this product in different Latin American countries / cultures / audiences such as the Mexican, Peruvian, Paraguayan , Argentina, among others. It is a fiction genre that has not only captivated audiences of diverse sociological characteristics, but has also collaborated with the construction of a symbolic bridge that contributes by diversifying the communication channels for a deepening of the dialogue between Korea and Latin America.